Ketahanan Pangan Rumah Tangga Petani Di Lahan Sawah Tadah Hujan (Studi Kasus Di Desa Sendangagung, Giriwoyo, Wonogiri) - Irvan Suryanto; Yoesti Silvana Arianti; Agung Setyarini (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2023)
Various problems in the agricultural sector include land conversion, climate change, water shortages, high input prices, and declining agricultural land productivity. Reduced production will affect farmers' income, which will impact the food security of farming households. The research aims to determine the proportion of food expenditure to total expenditure and assess the food security of farming households. The research location was chosen purposively, namely in Giriwoyo District, where most of the agricultural land is rain-fed. The sampling method used simple random sampling with a total of 30 farming households as respondents. Analysis of farmer household food security using cross-classification of food expenditure shares and energy adequacy levels. Energy and protein consumption levels were calculated using the 24-hour recall method. The research results explain that the average proportion of food expenditure to the total expenditure of farmer households is 55.61%, which shows that the level of farmer welfare is quite high. The food security conditions of rice farming households are based on levels, namely food security at 80%, food insecurity at 16.67%, and 3.30% of farming households are declared food deficient. To maintain or increase the food security of farming households, local food diversification is needed so that farming households do not only depend on rice as a source of carbohydrates. Counseling needs to be carried out to increase knowledge regarding the consumption of nutritious, diverse, balanced, and safe food.